Experimental evidence on public good behavior across Pakistan’s fractured educational system - Aftab, Zehra (International Food Policy Research Institute, 2016)
This paper adopts identity as a core concept. Following Akerlof and Kranton (2010), it demonstrates how our social identities, and not just economic incentives, influence our decisions. I acknowledge that identity is a multi-layered concept incorporating not only a social dimension (class and gender), but also has ideological (religious orientation) and linguistic dimensions. The paper argues that, even within the same respective identity group, context is important, in the sense that decisions vary based on who one interacts with, their identity, and their respective actions.